Infected Renal Cyst as a Complication of Dropped Gallstones during Laparoscopic Cholecystectomy. (30th September 2018) - Kennedy-Snodgrass, Chelsea; Keenan, Vivian; Katz, Douglas S.
Abstract : Dropped gallstones are a relatively common complication, occurring in 3% to 32% of laparoscopic cholecystectomies performed, depending on various intraoperative risk factors. However, complications arising from dropped gallstones are relatively rare, occurring in fewer than 1% of such patients, and can include abscesses and inflammatory masses confined to the subhepatic space, presenting days to years later. We report a patient who developed an infected renal cyst as a result of dropped gallstones, which created a fistula from the duodenum to a previously simple right renal cyst, which was initially identified on an abdominal CT scan. Dropped gallstones can result in substantial morbidity in a minority of patients following cholecystectomy performed for cholecystitis, and a high clinical as well as radiological index of suspicion may be required for accurate early recognition and treatment.